2021
DOI: 10.1038/s41598-021-81682-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing three Dragon fruit (Hylocereus spp.) species grown in Andaman and Nicobar Islands of India using morphological, biochemical and molecular traits

Abstract: Dragon fruit (Hylocereus spp.), an important tropical fruit belonging to the family Cactaceae, is rich in essential nutrients such as vitamins, minerals, complex carbohydrates, dietary fibres and antioxidants. This study aims to distinguish three dragon fruit species well adapted to Andaman and Nicobar Island through morphological (34 quantitative and 26 qualitative traits), biochemical (5 traits) and molecular (14 ISSR primers) characterization. Morphological characterization revealed that presence of conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 53 publications
3
37
2
3
Order By: Relevance
“…and Megalanthus spp. [8,17]. In this study, the genotypes showed the shape of margin between areolas between concave and right, contrary to that reported in other studies on different species of Hylocereus, where the predominant forms were convex, with the presence of wax [8].…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…and Megalanthus spp. [8,17]. In this study, the genotypes showed the shape of margin between areolas between concave and right, contrary to that reported in other studies on different species of Hylocereus, where the predominant forms were convex, with the presence of wax [8].…”
Section: Discussioncontrasting
confidence: 91%
“…None of the genotypes had wax but there was variation for each of the categories of the morphological descriptors evaluated. It was stated by [8] that cladode, floral and fruit characteristics of H. megalanthus, such as margin ribs of cladode, waxiness, sepal color, color of ring at base of reproductive organs in flower, fruit shape, position towards peel, pulp color, peel color and seed size are visible taxonomic traits to distinguish this species from two Hylocereus spp. : H.undatus and H. costariscensis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Selenicereus species, some studies focused on the morphology and Inter-simple sequence repeat (ISSR marker) for genetic diversity and species identification (Tao et al 2014;Abirami et al 2021). However, morphological traits influenced by environmental factors and the band pattern may not be reliable because ISSR is a dominant marker.…”
Section: Introductionmentioning
confidence: 99%